2023
DOI: 10.1021/acs.nanolett.3c01878
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Cell Armor Made of DNA Origami

Abstract: The bioengineering applications of cells, such as cell printing and multicellular assembly, are directly limited by cell damage and death due to a harsh environment. Improved cellular robustness thus motivates investigations into cell encapsulation, which provides essential protection. Here we target the cell-surface glycocalyx and cross-link two layers of DNA nanorods on the cellular plasma membrane to form a modular and programmable nanoshell. We show that the DNA origami nanoshell modulates the biophysical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Future investigations are needed to elucidate the underlying mechanism responsible for this phenomenon. Although the focus of this study is on enhancing the cellular uptake of DNs, it has been shown that the cross-linking of DNs to form higher-order assemblies may lead to a reduction in DN internalization and an increase in their cell-surface retention time, compared to individual single DN species . It seems the modulation of DN cellular internalization may be achieved through tuning the interactions between DNs and cell membranes for either speeding up or slowing down the process.…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations are needed to elucidate the underlying mechanism responsible for this phenomenon. Although the focus of this study is on enhancing the cellular uptake of DNs, it has been shown that the cross-linking of DNs to form higher-order assemblies may lead to a reduction in DN internalization and an increase in their cell-surface retention time, compared to individual single DN species . It seems the modulation of DN cellular internalization may be achieved through tuning the interactions between DNs and cell membranes for either speeding up or slowing down the process.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-based materials possess exceptional programmability, allowing for precise structural customization and adjustable properties. , Combined with their inherent biocompatibility, DNA-based materials have been successfully used for cell encapsulation, cell culture, tissue engineering, vaccine adjuvant, and drug delivery . Recently, building multicellular assemblies by using DNA networks is receiving increasing attention due to their powerful programmability to form cell clusters for encoding cell–cell interactions. Interestingly, different DNA architectures have been successfully used to enhance cell clustering in vitro .…”
Section: Introductionmentioning
confidence: 99%